Denial of Child Maltreatment Histories among Male Adolescent Offenders - YalÄ±m, AslÄ± Cennet; Sezgin, A. Ufuk (International Journal of Criminology and Sociology, 2015)
This paper aims to explore relationship between childhood maltreatment histories and denial of male adolescent offenders who are imprisoned for violent criminal behaviors. The study group consists of 235 male adolescents between the ages of 15 and 18 in İstanbul Bayrampaşa H Type Prison affiliated to the Ministry of Justice. According to the results, one hundred and thirty-seven children have child abuse and neglect (CAN) histories and there is no significant relationship between violent criminal behavior and being exposed to CAN. However, responses of adolescents indicate that they tend to deny CAN histories when being asked direct questions regarding violence compared to indirect questions. Additionally, the results of Childhood Trauma Questionnaire (CTQ)’s Minimization/Denial subscale show that 71% of the study group has sufficient scores for possible underreporting of maltreatment. This study can provide guidance to clinicians, who are going to conduct a study on adolescents with maltreatment histories, regarding possible tendency of denial.